حوار الأديان بين بناء جسور التفاهم وحفظ الهوية (Inter-religious dialogue between building bridges of mutual understanding and preservation of identity) - Thoha, Anis Malik (International Islamic University Malaysia, IIUM Press, 2010)
Inter-religious dialogue has been among the crucial issues since the early 20th century. Seminars and conferences on this issue have been conducted with the special agenda to embark on serious ways for building mutual understanding between the followers of different religions. Now, inter-religious dialogue has become more important as religion has been charged of being the agent behind the bloody wars, genocide, and every human catastrophe, such as the tragedy of 9/11. Therefore, this article is an attempt to analyse the issues pertaining to the concepts,principles, objectives, approaches and organization of inter-religious dialogue in the light of the increasing global phenomenon of utilizing this means to promote certain vested interests, to dilute cultural identities of certain peoples, and to win the “war of ideas”. The main argument in this essay is that for any interreligious dialogue to achieve its noble objectives mentioned above, it is necessary that it be established on sound and non-partisan principles and guidelines.